Analysis and Evaluation of Seed-Filling Performance of a Pneumatic Interference Precision Seeder for Small Cabbages - Xiong Liu; Chunjian Su; Zhongyang Li; Kai Wang; Fuxiang Xie; Yanan Tian; Jiangtao Qi (Applied Sciences, 2024)
To address the current problems of poor seed-filling performance and seed leakage of the pneumatic seed filler for cabbage, we designed a pneumatic disturbing precision seed filler for cabbage based on the auxiliary disturbing seed-filling method. This seeder can completely perturb the seed population entering the bottom of the seed box casing during the seed-filling process, thereby increasing the initial velocity of the cabbage seeds, and facilitating the smooth progress of the seed-filling process. Firstly, we carried out a theoretical analysis based on the particle dynamics of the seed-filling process of the seeder and obtained the influencing factors affecting the seed-filling performance of the seeder. Secondly, through EDEM discrete element simulation, the average speed of the seed population, the disturbance frequency, and the degree of disturbance were used as the indicators to select the seed discharge disk structure with the best seed-filling performance. In the experimental aspect, a four-factor three-level orthogonal standardized test was conducted to evaluate the seed filling performance of the planter, using the seed suction qualification rate and the seed leakage rate as the evaluation indexes. The optimal structure of the seed discharge tray was selected through polarity analysis and ANOVA. The optimal combination of parameters for the seed-filling process of the planter was obtained; linear serrated disk, 40 rpm disk rotation speed, −2500 Pa negative fan pressure, and 1.2 mm aperture diameter. After comparative validation tests, the seed suction qualification rate of the seed absorber was 95.32%, and the leakage rate was 3.11%, which was in line with the agronomic planting of Chinese cabbage seeds.